2018
DOI: 10.1371/journal.pone.0202038
|View full text |Cite
|
Sign up to set email alerts
|

Why large seeds with physical dormancy become nondormant earlier than small ones

Abstract: Under natural conditions, large seeds with physical dormancy (PY) may become water permeable earlier than small ones. However, the mechanism for this difference has not been elucidated. Thus, our aim was to evaluate the traits associated with PY in seeds of Senna multijuga (Fabaceae) and to propose a mechanism for earlier dormancy-break in large than in small seeds. Two seedlots were collected and each separated into large and small seeds. Seed dry mass, water content, thickness of palisade layer in the hilar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…lens, hilum and pleurogram. Unlike breaks in the lens (Rodrigues-Junior et al, 2018), breaks in the pleurogram were not indicated by a clear decrease in palisade layer thickness. Irwin and Barneby (1982) described the morphology of seeds of 146 Senna species from the New World, 76 % of which had a pleurogram.…”
Section: Discussionmentioning
confidence: 67%
“…lens, hilum and pleurogram. Unlike breaks in the lens (Rodrigues-Junior et al, 2018), breaks in the pleurogram were not indicated by a clear decrease in palisade layer thickness. Irwin and Barneby (1982) described the morphology of seeds of 146 Senna species from the New World, 76 % of which had a pleurogram.…”
Section: Discussionmentioning
confidence: 67%
“…Taylor, 2005;Zeng Seed Science Research 279 et al, 2005). Rodrigues-Junior et al (2018b; 2) state 'it is rather difficult to detect a relationship between seed coat thickness and level of dormancy'. Some studies of Caesalpinioideae and Mimosoideae species have related palisade thickness to water impermeability (e.g.…”
Section: Palisade Thicknessmentioning
confidence: 99%
“…Thus, soil humidity is a key factor modulating the germination timing of some water-impermeable seeds. In this way, studies have investigated this water-dependent mechanism to break PY and related it to the increasing internal vapour pressure in the seed caused by the association between humidity and high temperatures, which dislodge the weak regions in the seed coat forming the water gap (see Rodrigues-Junior et al 25 and Jayasuriya et al 63 ).…”
Section: Resultsmentioning
confidence: 99%
“…of this kind of dormancy [21][22][23][24][25] and an investigation on water-impermeable seeds in this genus may allow new advances in the evolution of this restrict coat-imposed dormancy. Thus, we addressed the following questions: (1) What is known about seed dormancy in Cassia?…”
mentioning
confidence: 99%